Fetal Maturation and Intrauterine Survival in Asian American Women by Ethnicity. Issue 9 (September 2022) - Dongarwar, Deepa; Maiyegun, Sitratullah O.; Yusuf, Korede K.; Al Agili, Dania E.; Salihu, Hamisu M.
Abstract : Maternal race/ethnicity is well established as a risk factor for adverse birth outcomes, such as stillbirth. Asian Americans in the United States are generally treated as a homogenous group, even though there are ethnic subgroups. The authors sought to determine whether fetal maturation, as captured by gestational age periods, influences the risk of stillbirth in Asian American fetuses in general as well as within different ethnic subgroups. Abstract: Objectives: Although there are multiple ethnic subgroups of the Asian race, this population is usually treated as homogenous in public health research and practice. There is a dearth of information on fetal maturation and perinatal outcomes among Asian American women compared with their non-Hispanic (NH) White counterparts. This study aimed to determine whether fetal maturation, as captured by gestational age periods, influences the risk of stillbirth in Asian American fetuses, in general, as well as within different ethnic subgroups: Asian Indian, Korean, Chinese, Vietnamese, Japanese, and Filipino, using NH Whites as referent. Methods: We included singleton births within 37 to 44 gestational weeks occurring in Asian American and NH White mothers from 2014 to 2017. Adjusted logistic regression models were used to quantify the association between mother's race/ethnicity and risk of stillbirth by gestational age phenotypes: early-term, full-term, late-term, and postterm. Results: Compared with NH Whites, Asian Americans had 35% (adjusted odds ratio 0.65, 95% confidence interval 0.53–0.76) and 28% (adjusted odds ratio 0.72, 95% confidence interval 0.59–0.85) lower risk of early-term and full-term stillbirths, respectively. Conclusions: Our study suggests the existence of differential maturation of the fetoplacental unit as explanation for the decline in intrauterine survival advantage with advancing gestational age among Asian American subgroups.